Comparing Facebook as an interactive communication tool for companies in LatAm and worldwide (Communication & Society, 2020)
Social networks have changed the communication rules between companies and their stakeholders. Facebook became an important tool of communication strategies to promote interaction and dialogue. The objective of this study is to analyze how companies in LatAm and worldwide are managing the interaction with their stakeholders on Facebook. For this paper, 159 corporate profiles and 32,760 posts were analyzed through the methodology of content analysis. The categories selected were communication approach, communication resources, interaction level, and interaction rate. Results illustrate that the communication of companies in LatAm and worldwide mainly involves an informative approach on Facebook. The content disseminated by companies is not promoting interaction with the stakeholders. In contrast, companies are managed in a unidirectional way, meaning that it is not managed to establish and strengthen relationships, but rather to get visibility.